Retirement in Non-Cooperative and Cooperative Families - Erik Hernæs; Zhiyang Jia; Steinar Strøm (Center for Economic Studies and ifo Institute (CESifo), 2001)
Models that allow for non-cooperative as well as cooperative behavior of families are estimated on data from Norway in 1993 and 1994. The husband is eligible for early retirement while the wife is not. The models aim at explaining labor supply behavior of married couples the first twelve months after the husband became eligible for early retirement. Estimates and predictions derived from the different models are compared. Yet, no definite conclusion is reached with respect to what model is best at explaining the observed behavior. The models are employed to simulate the impacts on labor supply of taxing pension income the same way as labor income. We find that that this change of the tax system may reduce the propensity to retire early considerably.
Keywords: 330; Family labor supply; retirement; econometric models; policy simulations